ХАЛЫҚ ПЕДАГОГИКАСЫНДА ЖАСЛАРҒА АДАМДЫ ЕМЛЕЎ ТӘЖИРИЙБЕЛЕРИН ҮЙРЕТИЎ ДӘСТҮРЛЕРИ - Курбанбаева, А.Ж. (ILIM hám JÁMIYET, 2020)
The article is devoted to the issues problems of treament experience of the who are treated mainly people, with the natural things that have medical properties.